Design and Implementation of Electric Steering Gear Inspection System for Unmanned Aerial Vehicles Based on Virtual Instruments - Zheng Xing; Yang He; Liang Shao Jun (MATEC Web of Conferences, 2016)
A kind of UAV electric servo detection system based on Virtual Instrument is designed in this paper, including the hardware platform based on PC-DAQ virtual instrument architecture and the software platform based on LabVIEW function, structure and system implementation methods. The function, structure and system implementation method of software platform is also described. The gear limits checking, zero testing, time domain characteristics test results showed that the system achieves testing requirements well, and can complete detection of electric steering gear automatically, fast, easy and accurate.